EFFECT OF BUFFALO SEMINAL PLASMA PROTEINS ON EPIDIDYMAL SPERMATOZOA MOTILITY DURING IN VITRO CAPACITATION - ARANGASAMY, A; SINGH, L P (The Indian Journal of Animal Reproduction, 2023)
This study was undertaken to observe the sperm motility response with the heparin binding proteins ·(HBPs) and gelatin binding proteins (GBPs) during in vitro capacitation. Washed buffalo epididymal sperms were incubated with heparin (10μg/ml) in the presence of HBPs and GBPs@ 10, 20, 30, 40, 50 and 60 μg/ml. The percentage of sperm motility was evaluated from O to 6 h. Both HBPs and GBPs acted in a similar way for maintaining the sperm motility during in vitro capacitation.
Keywords: In vitro capacitation; Heparin; Gelatin; Proteins; Buffalo; Epididymal spermatozoa